Design and Creation of Android-Based Learning Media in Informatics Subjects in Vocational High Schools - Prayudha, Agung Rorhi; Alfandri, Heru; Gunawan, Roni Arya (JURNAL PTI (PENDIDIKAN DAN TEKNOLOGI INFORMASI) FAKULTAS KEGURUAN ILMU PENDIDIKAN UNIVERSITA PUTRA INDONESIA "YPTK" PADANG, 2024)
This research aims to determine the validity, practicality and effectiveness of designing and making android-based Learning Media in Class X Informatics Subjects at SMK N 9 Padang for the 2022/2023 Academic Year. This research uses the development research method (Research & Development). The sample in this study consisted of 35 vocational school students. This research method uses analysis (ADDIE), with the design and development steps as follows. (1) Analyze, (2) Design, (3) development, (4) Implement, and (5) Evaluate. The results of the validity test by experts, the overall validator test assessment of Android-based learning media in the Class X Informatics subject at SMK Negeri 9 Padang was 87.11%, so the validity level can be interpreted as valid for use. The results of the overall practicality test assessment of the Android-based Learning Media in the Informatics subject Class The results of the overall effectiveness test assessment of the effectiveness of Android-based learning media in the Informatics subject Class In conclusion, based on assessments along with expert input and the results of field trials, Android-based learning media as a learning medium has been tested for its suitability, superiority and can be used in the learning process in class X Informatics subjects at SMK Negeri 9 Padang.